2012
DOI: 10.1177/0269881111434619
|View full text |Cite
|
Sign up to set email alerts
|

The panicolytic-like effect of fluoxetine in the elevated T-maze is mediated by serotonin-induced activation of endogenous opioids in the dorsal periaqueductal grey

Abstract: Serotonin (5-HT), opioids and the dorsal periaqueductal grey (DPAG) have been implicated in the pathophysiology of panic disorder. In order to study 5-HT-opioid interaction, the opioid antagonist naloxone was injected either systemically (1 mg/kg, i.p.) or intra-DPAG (0.2 μg/0.5 μL) to assess its interference with the effect of chronic fluoxetine (10 mg/kg, i.p., daily for 21 days) or of intra-DPAG 5-HT (8 μg/0.5 μL). Drug effects were measured in the one-escape task of the rat elevated T-maze, an animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…These findings are a first indication of interaction between 5-HT and opioids in the DMH. Similar results have been reported in the DPAG with escape performed in the elevated T-maze test (Roncon et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are a first indication of interaction between 5-HT and opioids in the DMH. Similar results have been reported in the DPAG with escape performed in the elevated T-maze test (Roncon et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The doses of the drugs used in all these experiments were selected on the basis of previous results with the DPAG (De Bortoli et al, 2013; Rangel et al, 2014; Roncon et al, 2012, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings have also shown that chronic pain corresponds with greater functional connections between the ventromedial PFC and PAG in humans (31), and robust mPFC-PAG projections have been confirmed in rodents (32). Rodent models of chronic pain and stress induce plasticity within the PAG (3335), and PAG activation modulates anxiety-like behaviors (36, 37). …”
Section: Introductionmentioning
confidence: 99%
“…These devices have been submitted to extensive ethological and pharmacological validation and are considered useful for the study of anxiolytic and panicolytic drugs. [1][2][3][4][5][6][7][8][9][10] For example, the EPM and ETM tests have been used to compare the effects of anxiolytic/panicolytic drugs delivered via systemic injection or microinjection into specific encephalic structures, [11][12][13][14][15][16] thereby facilitating the study of the neuroanatomical basis of fear-and anxiety-induced reactions 17,18 and the establishment of correlations between behavioral responses and different stress-related models. [19][20][21] More recently, prey-versus-predator paradigms have also been used to investigate innate and conditioned fearrelated reactions and the effects of drugs that act in the neural substrates of aversive stimulus-induced emotional responses.…”
Section: Introductionmentioning
confidence: 99%